2020
DOI: 10.1073/pnas.2020315117
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailable soil Pb minimized by in situ transformation to plumbojarosite

Abstract: Exposure to lead (Pb) during early life has persistent adverse health effects. During childhood, ingestion of bioavailable Pb in contaminated soils can be a major route of Pb absorption. Remediation to alter physiochemical properties of soil-borne Pb can reduce Pb bioavailability. Our laboratory-based approach for soil Pb remediation uses addition of iron (Fe) sulfate and application of heat to promote formation of plumbojarosite (PLJ), a sparingly soluble Pb-Fe hydroxysulfate mineral. We treated two soils wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 48 publications
4
36
0
Order By: Relevance
“…For either treated soil, the Pb RBA was <1%. Reduced Pb bioavailability of both treated BHK soils was consistent with recent work that found treatment to promote PLJ formation decreased Pb bioavailability in another set of test soils . Notably, results of the current study and earlier work cited here show that the formation of PLJ significantly decreases Pb bioavailability .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…For either treated soil, the Pb RBA was <1%. Reduced Pb bioavailability of both treated BHK soils was consistent with recent work that found treatment to promote PLJ formation decreased Pb bioavailability in another set of test soils . Notably, results of the current study and earlier work cited here show that the formation of PLJ significantly decreases Pb bioavailability .…”
Section: Resultssupporting
confidence: 92%
“…Reduced Pb bioavailability of both treated BHK soils was consistent with recent work that found treatment to promote PLJ formation decreased Pb bioavailability in another set of test soils . Notably, results of the current study and earlier work cited here show that the formation of PLJ significantly decreases Pb bioavailability . By contrast, remediation of soils with phosphate had much more modest effects on Pb bioavailability in the mouse model. , These findings suggested that PLJ formation may be a superior method for remediation of Pb-contaminated soils, if scalable to field applications.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Pb(II) is hard to migrate and degrade, which have become an important cause of Pb(II) pollution in soil, water, air, and many other places. [5][6][7][8][9][10][11][12][13] Lead (II) exists in the environment will eventually be transmitted to plants and the human body through the food chain, [14][15][16][17][18][19] causing damage to organs [20] and hormone levels. [21] For children, a very small amount of Pb(II) may inhibit their brain development, [22] break their bones, [23] even damage their DNA.…”
Section: Introductionmentioning
confidence: 99%